(untitled) (Al-Academy, 2024)
Designer Alexander McQueen has unusual intellectual interventions and formal formulations in his fashion designs, which are characterized by the fusion between reality and imagination, which includes a group of overlapping and intertwined relationships, which created a problem for the concept of merging the concepts of formal reality and imaginative thinking and the coupling processes between them in forming fashion design. The problem was defined as the following question: “What are the mechanisms of merging reality and imagination and its intellectual and practical implications in a collection of fashion designs?” The goal was to reveal a fusion between formal reality and mental imagination in a collection of women’s fashion designs by designer Alexander McQueen. The research community was divided and sampled into three stages within the period (1996-2010), to reach the most important conclusions: _ The duality of form and content formed a different fusion to form fashion by making the strange form familiar, and making the familiar form strange, by adopting the realistic form of the familiar nature, combined with the imaginative data of the designer and the effects of his psychological emotions, causing astonishment and shock to the contents of the fashion. Elements of forming fashion designs were built on the basis of inspiration from stories, an event, or an experience with a visual vision of realistic objects and shapes that stimulate the imagination of the designer on the idea he imagined and based on his creative ability towards fashion design.